The effect of foreign bank presence on firm entry and exit in transition economies - Olena Havrylchyk (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This study investigates the impact of foreign bank penetration on firm entry in Central and Eastern Europe. Acquisition of domestic banks by foreign investors has lowered rates of firm creation, decreased the average size of entrants, and increased firm exit in industries with greater informational opacity, while entry of greenfield foreign banks appears to have spurred firm creation and exit. We modify the view in earlier studies that informational opacity equates with firm size, defining opacity in terms of technological characteristics for a given industry. We find the economic significance of foreign bank entry is larger for opaque industries than industries with large shares of small firms. The study provides evidence of increased credit constraints for start-ups in Central and Eastern Europe, which is consistent with the theoretical proposition that the presence of foreign banks exacerbates informational asymmetries.
URN:NBN:fi:bof-201408072008
Keywords: E51; G21; M13; 330; Entrepreneurship; Foreign bank entry; Asymmetric information; Credit constraints